2020
DOI: 10.1055/s-0040-1717098
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Nonoptimal Cervicovaginal Microbiota and Psychosocial Stress on Recurrent Spontaneous Preterm Birth

Abstract: Objective While select cervicovaginal microbiota and psychosocial factors have been associated with spontaneous preterm birth, their effect on the risk of recurrence remains unclear. It is also unknown whether psychosocial factors amplify underlying biologic risk. This study sought to determine the effect of nonoptimal cervicovaginal microbiota and perceived stress on the risk of recurrent spontaneous preterm birth. Study Design This was a secondary analysis of a prospective pregnancy cohort, Mothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…This agreement is more remarkable as that cohort was restricted to women with a prior history of sPTB who received progesterone therapy in the subsequent pregnancies that comprise their cohort ( Callahan et al., 2017b ). Also, in a study restricted to women with a prior sPTB, vaginal CST IV was found to be a significant risk factor for a recurrent sPTB ( Gerson et al., 2020 ). Conversely, studies that have considered substantial numbers of cases of PTB among AA women did find particular taxa that increased the risk of PTB, whereas our study did not.…”
Section: Discussionmentioning
confidence: 99%
“…This agreement is more remarkable as that cohort was restricted to women with a prior history of sPTB who received progesterone therapy in the subsequent pregnancies that comprise their cohort ( Callahan et al., 2017b ). Also, in a study restricted to women with a prior sPTB, vaginal CST IV was found to be a significant risk factor for a recurrent sPTB ( Gerson et al., 2020 ). Conversely, studies that have considered substantial numbers of cases of PTB among AA women did find particular taxa that increased the risk of PTB, whereas our study did not.…”
Section: Discussionmentioning
confidence: 99%
“…A nonoptimal CST IV cervicovaginal microbiome is common in Black women and has been associated with negative maternal-child health outcomes, including obstetric complications, spontaneous preterm birth, and neonatal morbidity and mortality (Brown et al, 2018(Brown et al, , 2018Callahan et al, 2017;DiGiulio et al, 2015;Elovitz et al, 2019;Fettweis et al, 2019;Florova et al, 2021;Gerson et al, 2020a;Hočevar et al, 2019;Ravel et al, 2011;Romero et al, 2014;Tabatabaei et al, 2019Tabatabaei et al, , 2019Zhou et al, 2007). This underlying biological risk is further amplified by a variety of environmental factors that contribute to a high risk in utero environment, including, but not limited to, obesity, diabetes and consumption of a diet that deficient in dietary fibers (Brookheart et al, 2019;Danese and Lewis, 2017;Gerson et al, 2020b;Shivakoti et al, 2020). While these maternal environmental perturbations alter the composition of the microbiota transferred from mother to offspring, the possibility that prenatal exposure to these risk factors may impact developmental processes that support offspring response and adaptation to postnatal colonization remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…During pregnancy, Black women are more likely to harbor CST IV microbiota that have been associated with increased incidence of obstetric complications, inflammation in the intrauterine environment, spontaneous preterm birth, and neonatal morbidity (Brown et al, 2018(Brown et al, , 2018Callahan et al, 2017;DiGiulio et al, 2015;Elovitz et al, 2019;Fettweis et al, 2019;Florova et al, 2021;Gerson et al, 2020a;Hočevar et al, 2019;Ravel et al, 2011;Romero et al, 2014;Tabatabaei et al, 2019Tabatabaei et al, , 2019Zhou et al, 2007). The risk associated with CST IV may be further amplified by a variety of environmental factors that promote chronic and systemic inflammation, including maternal stress and trauma, infection, and consumption of a high-fat, low-fiber diet (Brookheart et al, 2019;Danese and Lewis, 2017;Gerson et al, 2020b;Shivakoti et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] High perceived stress during pregnancy has also been associated with obstetrical complications, such as gestational diabetes mellitus, preterm birth, gestational hypertension, preeclampsia and complications for the infant, such as being small for gestational age. [7][8][9][10][11] The way that stress is experienced and expressed and the resulting physical and mental health effects is highly individualized, and may be influenced by culture. The data-driven Woods-Giscombe's Superwoman schema explains that Black women feel an obligation to manifest strength and independence, suppress emotions, including reporting perceived stress, succeed despite limited resources, and help others, 12 but the combined effects of structural inequities and chronic experienced stress explain poorer health.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] There is increasing evidence that the microbiota-gut-brain axis, that encompasses interactions between the neurological, endocrinological and immunological systems, is associated with mental health disorders and obstetrical complications. 10,[19][20][21][22][23][24] The microbiota that reside in the gastrointestinal system can be influenced by lifestyle (e.g., diet, exercise), residential location and home environment (e.g., rural versus urban), and medication use (e.g., antibiotics). 25 Disruptions in the gut microbial ecosystem have been associated with both intestinal and systemic diseases (e.g., IBS, diabetes, depression).…”
Section: Introductionmentioning
confidence: 99%